Work Discipline Mechanism on Employee Performance: The Mediating Role of Organizational Commitment in the Public Sector - Liana, Yuyuk; Kurnianing Putri , Siti Aisyah; Irawati, Rina; Rachmania, Benita (Universitas Muhammadiyah Pontianak, 2026)
Employee performance in public organizations remains a critical issue, particularly regarding work discipline and organizational commitment. This study aims to examine the effect of work discipline on employee performance through organizational commitment. A quantitative approach was employed using SEM-PLS to analyze data from 53 employees of the Manpower, Investment, and One-Stop Integrated Service Office of Malang City selected through saturated sampling. The results indicate that work discipline positively affects employee performance and organizational commitment, while organizational commitment positively influences performance and mediates the relationship. These findings imply that strengthening discipline and commitment is essential for sustainable performance improvement.